Syndromic hearing loss: An update. (September 2013) - Castiglione, Alessandro; Busi, Micol; Martini, Alessandro
Abstract: Hearing impairment is one of the commonest clinical conditions. It has been estimated that approximately 1 in 10 persons has hearing concerns. Further epidemiological studies have found that the percentage of the general population with hearing loss greater than 45 dB HL and 65 dB HL is 1.3% and 0.3%, respectively, between 30 and 50 years of age; and 2.3% and 7.4% between 60 and 70 years of age. The prevalence of childhood and adolescent hearing loss is around 3%. At birth, between one and two out of 1000 newborns are affected by hearing loss of such a degree as to require treatment (auditory training and rehabilitation, hearing aids or cochlear implantation). To summarize, hearing impairment affects up to 30% of the international community and estimates indicate that 70 million persons are deaf. The causes of hearing loss differ and they can vary in severity and physiopathology. In many cases it is not possible to define a definite aetiology. Nevertheless, it is known that most are due to a genetic cause and among these the majority appear in a non-syndromic form. The aetiology of hearing loss in children is unknown in 40% of cases, genetic non-syndromic in 30%, and genetic syndromic in 3–5%. The two most common genes involved in hearing loss are GJB2 and SLC26A4 . Mutations in these genes can be responsible for syndromic hearing loss, as keratitis ichthyosis deafness (KID) and Pendred syndromes, respectively, or non-syndromic hearing loss (as DFNB1 and DFNB4, respectively). DFNB1 with GJB2 mutations is the most common non-syndromic form and Pendred syndrome is the most common syndromic form. Neither of these last two is usually characterized by congenital macroscopic dysmorphic features, and affected children can be generally considered as well babies. Nonetheless, 2–4% of live births have congenital malformations, most commonly caused by multifactorial defects, followed by chromosomal disorders, single gene mutations and teratogens (alcohol, drugs). Some of these conditions could directly affect the auditory system and be responsible for sensorineural, conductive or mixed hearing loss. The London Dysmorphology Database lists approximately 400 syndromes that include hearing loss among the clinical features. Other conditions such as cystic fibrosis are not usually responsible for hearing loss but they can indirectly affect the auditory system as a consequence of the management of the disease. Other systemic disorders can lead to hearing impairment when the disease involves a part of the auditory system from the external ear to the auditory cortex. From this standpoint there are a huge number of syndromes or conditions that can directly or indirectly cause hearing impairment. They can be responsible for congenital or prelingual, progressive and post-lingual hearing loss, with sensorineural, mixed or conductive deficits. In this updating research we have focused on syndromic forms that are known to be associated with hearing loss or that directly affect the auditory system. Some conditions of particular interest, or with high incidence, are also included.